Human papillomavirus (HPV)‐independent vulvar squamous cell carcinoma has a worse prognosis than HPV‐associated disease: a retrospective cohort study. Issue 2 (23rd May 2017) - McAlpine, Jessica N; Leung, Samuel C Y; Cheng, Angela; Miller, Dianne; Talhouk, Aline; Gilks, C Blake; Karnezis, Anthony N
Abstract : Aims: Vulvar squamous cell carcinoma (VSCC) can be subdivided by human papillomavirus (HPV) status into two clinicopathological entities. Studies on the prognostic significance of HPV in VSCC are discordant. Methods and results: We performed a retrospective analysis of overall survival (OS), disease‐specific survival (DSS) and progression‐free survival (PFS) in 217 patients with VSCC. Cases were extracted from an era of more aggressive en‐bloc radical dissections (1985–95) and more localized radical surgery through separate vulvar and groin excisions (1996–2005). p16 immunohistochemistry was used as a surrogate for HPV status. HPV status could be determined in 197 tumours, 118 HPV‐independent and 79 HPV‐associated tumours. Patients with HPV‐associated tumours were younger (mean 58.8 versus 71.6 years for HPV‐independent tumours, P < 0.0001) and more likely to have prior abnormal cervical cytology (41.1 versus 5.6% for HPV‐independent tumours, P < 0.0001). In univariable analysis, patients with HPV‐associated tumours had superior PFS [hazard ratio (HR): 0.37, 95% confidence interval (CI): 0.18–0.70], DSS (HR: 0.19, 95% CI: 0.08–0.41) and OS (HR: 0.35, 95% CI: 0.21–0.59). This was driven by worse outcomes (PFS, DSS and OS) for patients with HPV‐independent tumours compared with HPV‐associated tumours who underwent surgery after 1995. After adjusting for age and stage in multivariable analysis, patients with HPV‐associated tumours showed superior PFS (HR: 0.25, 95% CI: 0.07–0.77) and DSS (HR: 0.21, 95% CI: 0.04–0.78). Conclusions: VSCC can be stratified into two prognostically different diseases based on p16 immunostaining. HPV status was associated only with prognosis in the cohort that underwent surgery after 1995, suggesting that more conservative surgery may have led to worse outcomes for patients with HPV‐independent tumours.